Effects of calcium salts of polyunsaturated fatty acids on productive and reproductive parameters of lactating Holstein cows - Reis, M. M. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Ranches, J. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2012)
Two experiments evaluated milk production, serum progesterone and insulin, and reproductive performance of lactating Holstein cows receiving or not receiving Ca salts of polyunsaturated fatty acids (PUFA), or receiving Ca salts of PUFA at different daily frequencies. In experiment 1, 1,125 cows randomly distributed in 10 freestall barns were enrolled. Barns were assigned randomly to receive a high-concentrate diet containing (PI?) or not containing (control, CON) 1.1% (dry matter basis) Ca salts of PUPA. Diets were offered 6 times daily, whereas the Ca salts of PUFA were included in the PF treatment in the first feeding of the day. In experiment 2, 1,572 cows were randomly distributed in 10 freestall barns, which were assigned randomly to receive a diet similar to PF, but with Ca salts of PUFA included only in the first feeding of the day (PF1X), or equally distributed across all 6 feedings (PF6X). During both experiments, cows were artificially inseminated 12 h after the onset of estrus. Once per month, cows that did not conceive to artificial insemination were assigned to a fixed-time embryo transfer protocol. Pregnancy was determined via transrectal ultrasonography 28 and 60 d after expected ovulation. Pregnancy loss was considered in cows that were pregnant on d 28 but nonpregnant on d 60. During both experiments, feed intake, milk yield, and milk protein and fat content were recorded weekly. Blood samples were collected concurrently with embryo transfer. During experiment 1, feed intake was similar between treatments. Compared with CON, PF cows had greater milk yield (37.8 vs. 35.3 kg/d), and reduced milk fat content (3.41 vs. 3.55%). However, PF cows had reduced pregnancy losses per service compared with CON (12.6 vs. 18.3%). Serum progesterone was greater and serum insulin tended to be greater in primiparous cows receiving PF compared with CON cohorts (4.50 vs. 3.67 ng of progesterone/mL, and 10.4 vs. 7.5 mu UI of insulin/mL). During experiment 2, no treatment effects were detected for feed intake, milk yield, or milk fat, whereas PF1X cows tended to have reduced pregnancy losses per service compared with PF6X (14.4 vs. 18.4%). In summary, feeding Ca salts of PUFA to dairy cows increased milk production, did not alter feed intake, and reduced pregnancy losses per service. Further, the total daily amount of Ca salts of RITA should be fed during the first feeding of the day to optimize its benefits on pregnancy maintenance of dairy cows.
Keywords: dairy cow; polyunsaturated fatty acid; production; reproduction